Characteristics of pregnant who received Emergency Obstetric Psychoprophylaxis in private sector as an alternative to comprehensive care - Morales Alvarado, Sabrina (2015)
The aim of this study was to determine the characteristics of a group of pregnant women in sub private sector who received Emergency Obstetric Psychoprophylaxis (EM-OPP) between July 2012 and June 2014, also know the reasons why they did not perform their integral prenatal preparation to timely gestational age, between the fifth and seventh month, according to general technical recommendations, age ranges and educational level. Were reviewed and assessed 168 medical records, noting that the age range was 15-45 years (mean: 30), educational attainment was distributed: incomplete secondary 0.6%, complete secondary 6% incomplete higher 15.4% and above 78% complete. According to their employment status, 69% were working during pregnancy. Regarding his prenatal emergency preparedness, it was found that 100% of mothers reported satisfaction in receiving EM-OPP, to feel calmer and safer to directions and contribute to its delivery. Finally, 94.6% received their PPO-EM during the last week of gestation while 5.4% during labor, and the type of delivery, 64% ended in vaginal birth and the rest via cesarean section. We conclude that the PPO-EM is a beneficial opportunity for pregnant women who were unable to make timely prenatal preparation, which states that it is never too late to get a good preparation, which was associated with a good perinatal outcome.